PENGARUH MODEL PEMBELAJARAN TIPE STUDENT FACILITATOR AND EXPLAINING TERHADAP HASIL BELAJAR MENGGAMBAR DENGAN PERANGKAT LUNAK SISWA KELAS XI SMK NEGERI 1 SUMATERA BARAT - 2106-2112, Imam Munandar (Universitas Negeri Padang, 2018)
Abstract—The aim of this research is to determine the achievement of student from student facilitator and expalining method, the resign of the research is most of study result under of passing grade in January-June. The low value of the student revealed when the researcher did PLK activities on January-June 2017. Research saw that the value of many students under the KKM was 78 with the number of the students who didn’t complete reach, 74,07%. Looking at this problem, so that researcher was interested to apply the method of learning student facilitator and explaining on drawing subject with software. The implementation of this learning model strategy was aimed to improve the result of studying on drawing subject with softwareThis research was conducted in SMK Negeri 1 West Sumatera TGB majoring class XI, it included exprimental methode with cooperative approach. Sampling in this research’s using simple random sampling technique. The procedure that be used is by giving pretest, tecated and posttest.The result was obtained from the improvement of studying, after the applied learning method, with the average for the cognitive aspect started with 69 and increased to 81 initially 43 increased to 71 and for thepsychomotor aspect initially 59 to 77.Based on the result above, it can be concluded thatthe student learning class XI TGB SMK N 1 West Sumatera increased after applying this method.Keywords:Learning Achievement,Student Facilitator and Explaining.